Research on the influence mechanism of classroom leadership of international Chinese language teachers on students' learning psychology and academic performance - Wenshu Duan (Environment and Social Psychology, 2025)
This study investigates the influence mechanism through which classroom leadership affects academic performance among international Chinese language learners, with learning psychology as a potential mediating pathway. The research addresses critical gaps in understanding how transformational leadership behaviors influence student psychological states and subsequent academic outcomes in cross-cultural language education contexts. A quantitative research design with supplementary qualitative components was employed involving 387 international Chinese language learners from universities across North America, Europe, and Asia-Pacific regions. Qualitative insights from open-ended survey questions provided contextual support for quantitative findings. Participants completed validated instruments measuring transformational leadership behaviors (inspirational motivation, intellectual stimulation, individualized consideration, and idealized influence), learning psychology dimensions (motivation, attitudes, and anxiety), and academic performance indicators (objective and subjective measures). Structural equation modeling served as the primary analytical approach, supplemented by correlation and regression analyses to examine complex relationships among constructs. The findings reveal significant positive associations between classroom leadership and learning psychology (r = 0.459, β = 0.594), and between learning psychology and academic performance (r = 0.627, β = 0.673). The mediation analysis demonstrates that the indirect effect (0.400) substantially exceeds the direct effect (0.245), with learning psychology accounting for approximately 62% of the total effect magnitude. The structural equation model achieves excellent fit indices (CFI = 0.952, RMSEA = 0.048, SRMR = 0.039), explaining substantial variance in learning psychology (R² = 0.353) and academic performance (R² = 0.487). These results confirm learning psychology as the primary mechanism through which instructional leadership influences student achievement. These findings align with social cognitive theory's core tenets, particularly reciprocal determinism. The significant mediation effect of learning psychology (62% of total effect) demonstrates how environmental factors (transformational leadership) influence personal factors (psychological states), subsequently affecting behavioral outcomes (academic performance). The substantial indirect effect indicates that teacher leadership operates primarily through student psychological processes rather than direct instructional mechanisms, consistent with social cognitive theory's emphasis on cognitive and affective mediating factors in learning and performance. The study contributes theoretical advances by integrating transformational leadership theory with social cognitive frameworks in international language education contexts, while providing practical implications for professional development programs emphasizing transformational leadership competencies to optimize student psychological well-being and academic outcomes in cross-cultural educational environments.